Peningkatan Kadar Malondialdehid (MDA) Akibat Paparan Asap Rokok - Sampurna, Sampurna; Masyhudi, Masyhudi; Pritasari, Alteriana Mydriati Sita; Zulaikhah, Siti Thomas; Pratama, Arrizki Azka Pratama (FORIKES, 2023)
Exogenous free radicals can come from exposure to cigarette smoke containing various hazardous chemical components. Free radicals cause oxidative stress and pathological conditions, such as lipid peroxidation, decreased antioxidant levels, protein oxidation and deoxyribonucleic acid. Lipid peroxidation is characterized by increased levels of malondialdehyde. The purpose of this study was to analyze the impact of cigarette smoke exposure on malondialdehyde levels in Wistar strain rats exposed to cigarette smoke. The design of this study was post-test only with control group. The sample of this study was 12 male Wistar strain rats kept in the laboratory. The sample criteria were rats weighing 150-200 grams and aged 2 months. The samples were divided into 2 groups randomly, namely group K1 (given standard feed et libitum + distilled water) and group K2 (given standard feed et libitum + distilled water + exposure to cigarette smoke 3 cigarettes / day). Treatment was given for 14 days. On the 15th day, blood samples were taken from mice to examine malondialdehyde levels using ELISA (Enzyme-Linked Immunosorbent Assay). Data were analyzed using the Mann-Whitney test. The results of the analysis showed that the average malondialdehyde levels in K1 were 1.54±0.55 mmol/L; while in K2 it was 9.77±4.32 mmol/L. The p-value of the comparative analysis was 0.004; which means there was a difference in malondialdehyde levels between the two groups. Furthermore, it was concluded that exposure to cigarette smoke increased malondialdehyde levels in Wistar strain mice.Keywords: cigarette smoke; malondialdehyde; free radicals ABSTRAK Radikal bebas eksogen dapat berasal dari paparan asap rokok yang mengandung berbagai macam komponen kimia berbahaya. Radikal bebas menyebabkan stres oksidatif dan keadaan patologis, seperti peroksidasi lipid, penurunan kadar antioksidan, oksidasi protein dan deoxyribonucleic acid. Peroksidasi lipid ditandai dengan meningkatnya kadar malondialdehyde. Tujuan penelitian ini adalah untuk menganalisis dampak paparan asap rokok terhadap kadar malondialdehyde pada tikus galur wistar yang dipapar asap rokok. Desain penelitian ini adalah post test only with control group. Sampel penelitian ini adalah 12 ekor tikus jantan galur wistar yang dipelihara di laboratorium. Kriteria sampel adalah tikus dengan berat badan 150-200 gram dan berumur 2 bulan. Sampel dibagi menjadi 2 kelompok secara random, yaitu kelompok K1 (diberi pakan standar et libitum + aquadest) dan kelompok K2 (diberi pakan standar et libitum + aquadest + paparan asap rokok 3 batang/hari). Perlakuan diberikan selama 14 hari. Pada hari ke-15, dilakukan pengambilan sampel darah tikus untuk pemeriksaan kadar malondialdehyde menggunakan ELISA (Enzyme-Linked Immunosorbent Assay). Data dianalisis menggunakan uji Mann-Whitney. Hasil analisis menunjukkan bahwa rerata kadar malondialdehyde pada K1 adalah 1,54±0,55 mmol/L; sedangkan pada K2 adalah 9,77±4,32 mmol/L. Nilai p dari analisis perbandingan adalah 0,004; yang berarti ada perbedaan kadar malondialdehyde di antara kedua kelompok. Selanjutnya disimpulkan bahwa paparan asap rokok meningkatkan kadar malondialdehyde pada tikus galur wistar.Kata kunci: asap rokok; malondialdehyde; radikal bebas